Analysis of Electric Bus Utilization for Urban Transport using Bus Route, Passenger Demand and Fuel Consumptuion (Blok M-Kota Corridor Case) - Prayudyanto, Muhammad Nanang; Murtejo, Tedy; Ramadan, Ponco Sadewo (Universitas Ibn Khaldun Bogor, 2023)
Buses as a means of public transportation can greatly reduce traffic problems in urban areas through the use of, among other things, innovative techniques and technologies. The development of innovative technologies increasingly oriented towards the electrification of vehicle propulsion systems is expected to lead to the reduction of harmful emissions, increased vehicle efficiency, improved performance, reduced fuel consumption, and reduced noise. This study aims to determine the comparison of Transjakarta electric buses with conventional buses owned by Transjakarta, identify and evaluate the condition of the electric bus side. This study uses quantitative methods. The results of the study show a comparison of the operational cost calculation as indicated by the calculation of direct costs and indirect costs. The unit price for a bus/km for a diesel bus is Rp. 51,796, on the electric bus Rp. 224,991, and BBG buses for Rp. 82,227. where in the comparison of BOK diesel buses are cheaper than electric buses and CNG. The most expensive cost is the replacement of spare parts, especially the price of the battery which needs to be replaced every 10 years. 3,876, while bbg buses require much cheaper, which is Rp. 630. The calculation results of the electric bus battery consumption on the use of 1 route with a distance of 30.8 on weekdays on average 11.5% while on weekends it is 9.5%. At the kWh consumption, the electric bus requires the consumption of kWh per trip with a distance of 31.4 km is 23.57 kWh. From this value, it is known that the efficiency is 1.3 km/1 kWh. In charging the battery, the average battery charging time on the electric bus is 134 minutes or about 2.23 hours.